PENGEMBANGAN MEDIA PEMBELAJARAN WEBSITE BERBASIS GOOGLE SITES SEBAGAI SUMBER BELAJAR MANDIRI PADA MATERI SISTEM PEREDARAN DARAH DI SMA NEGERI 1 TELAGA BIRU - Dondo, Bahtiar; Nusantari, Elya; Ibrahim, Mustamin (Jurnal Biogenerasi, 2025)
This study aims to evaluate the validity and practicality of a Google Sites-based website as a self-learning resource for students studying the circulatory system topic. The study employed a Research and Development (R&D) method using the 4D model, which includes the stages of Define, Design, and Develop. However, this study does not involve the stage of Disseminate. Data collection techniques involved expert validation sheets and student response questionnaires. A limited trial was conducted with 30 Grade XI students at SMA Negeri 1 Telaga Biru. The results showed that content validation received a score of 72.22% (Valid), media validation scored 92% (Highly Valid), and student responses reached 85.23% (Highly Feasible). Based on these results, it can be concluded that the Google Sites-based learning media meets the criteria for validity and practicality, making it suitable for supporting the learning process and serving as an effective self-learning resource for students studying the circulatory system at SMA Negeri 1 Telaga Biru.